"Benifuuki" green tea, containing O-methylated EGCG, reduces serum low-density lipoprotein cholesterol and lectin-like oxidized low-density lipoprotein receptor-1 ligands containing apolipoprotein B: A double-blind, placebo-controlled randomized trial. (August 2016) - Imbe, Hisashi; Sano, Hiroyuki; Miyawaki, Masahiro; Fujisawa, Reiko; Miyasato, Mai; Nakatsuji, Fumihiko; Haseda, Fumitaka; Tanimoto, Keiji; Terasaki, Jungo; Maeda-Yamamoto, Mari; Tachibana, Hirofumi; Hanafusa, Toshiaki
Highlights: This is the first report on the effect of methylated catechins on lipid metabolism in humans. "Benifuuki" green tea is unique in containing high amount of methylated catechins. "Benifuuki" green tea significantly reduced serum total cholesterol, LDL cholesterol, and LAB levels. "Benifuuki" green tea may contribute to preventing cardiovascular diseases by lowering serum LDL cholesterol and LAB levels. Abstract: Dyslipidaemia is a significant cardiovascular risk factor. Green tea catechins are known to have cholesterol-lowering effects. We investigated the beneficial effects of "Benifuuki, " containing O -methylated catechin, on cardiovascular risk factors, specifically low-density lipoprotein (LDL) cholesterol levels. One-hundred fifty-five participants who met the inclusion criteria were divided into 3 groups: "Benifuuki, " "Yabukita, " or barley infusion drinkers. We evaluated the changes in parameters after 12 weeks. Serum LDL cholesterol levels in the "Benifuuki"-consuming participants were significantly lower than those in barley infusion-consuming participants without a green tea habit. Furthermore, the lectin-like oxidized low-density lipoprotein receptor-1 containing apolipoprotein B (LAB) levels in "Benifuuki" drinkers were significantly lower than those in the barley infusion group and the "Benifuuki" baseline LAB level. In participants without a green tea habit, "Benifuuki" significantly reduced the serum LDL cholesterol level and the LAB levels compared to those observed after barley infusion consumption.